Proceedings of the 12th ACM Conference on Electronic Commerce 2011
DOI: 10.1145/1993574.1993588
|View full text |Cite
|
Sign up to set email alerts
|

On the efficiency of equilibria in generalized second price auctions

Abstract: In sponsored search auctions, advertisers compete for a number of available advertisement slots of different quality. The auctioneer decides the allocation of advertisers to slots using bids provided by them. Since the advertisers may act strategically and submit their bids in order to maximize their individual objectives, such an auction naturally defines a strategic game among the advertisers. In order to quantify the efficiency of outcomes in generalized second price auctions, we study the corresponding gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
0
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 28 publications
4
107
0
2
Order By: Relevance
“…This is a typical assumption in the Bayes-Nash price of anarchy literature [1,3,6,10,19,21,22] with [2] being the only exception we are aware of. Unfortunately, our proof of the pure Bayes-Nash price of anarchy bound does not carry over to the case of correlated valuations either (for the same reason mentioned above).…”
Section: Lemma 52mentioning
confidence: 89%
See 2 more Smart Citations
“…This is a typical assumption in the Bayes-Nash price of anarchy literature [1,3,6,10,19,21,22] with [2] being the only exception we are aware of. Unfortunately, our proof of the pure Bayes-Nash price of anarchy bound does not carry over to the case of correlated valuations either (for the same reason mentioned above).…”
Section: Lemma 52mentioning
confidence: 89%
“…Instead, it resorts to bounding the utility of each player by appropriately selected deviations which reveal a relation between the social welfare at equilibrium and the optimal social welfare. This approach has been used in a series of papers that mostly focus on auctions (e.g., see [1,2,3,6,10,19,22]) and is actually the approach we follow in the current paper as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lucier and Borodin studied Bayes-Nash Equilibria of non-truthful auctions based on greedy allocation algorithms [16]. Paes Leme and Tardos [20], Lucier and Paes Leme [17] and Caragiannis et al [4] studied the ineffficiency of Bayes-Nash equilibria of the generalized second price auction. Roughgarden [22] showed that many price of anarchy bounds carry over to imply bounds also for learning outcomes.…”
Section: Related Workmentioning
confidence: 99%
“…Other recent papers study simple auctions used in practice and show that high social welfare can be achieved even when players' valuations come from arbitrarily correlated distributions [Lucier and Paes Leme 2011;Caragiannis et al 2012].…”
Section: Introductionmentioning
confidence: 99%